Chemistry education students’ difficulties in understanding English literature - Hana, Angelina Engrita Rambu; Nindya, Gabriela Yulianty; Gulo, Monica Friska; Wijayanti, Lucia Wiwid (Proceedings of International Conference on Research in Education, 2025)
Chemistry education students often face challenges in comprehending English-language literature, although most chemistry literature is published in English. These difficulties lead to reluctance in reading, as the material is considered complex and time-consuming, potentially hindering optimal development of scientific knowledge. This literature review analyzes seven journal articles to identify the difficulties, contributing factors, and impacts experienced by chemistry education students in understanding English-language literature. The results indicate that students struggle with grasping main ideas, implied information, and vocabulary. The implementation of basic English courses has been shown to improve students’ abilities, as evidenced by enhanced vocabulary, reading, and writing skills, and positive responses to effective, easy-to-understand, and useful teaching methods. Therefore, while challenges remain, learning basic English plays a crucial role in enhancing chemistry education students’ ability to comprehend scientific literature.